2007
DOI: 10.7150/ijms.4.190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1,25-dihydroxy-vitamin D3 in experimental sepsis

Abstract: Background: In addition to the regulation of calcium homeostasis, vitamin D affects the cellular immune system, targets the TNF-α pathway and increases vasoconstrictor response to angiotensin II. We therefore examined the effect of 1,25-dihydroxy-vitamin D 3 on coagulation and organ failure in experimental sepsis in the rat. Methods: Three series of placebo-controlled studies were conducted. All rats were pre-treated with daily SC injections of 1,25-dihydroxy-vitamin D 3 100 ng/kg or placebo vehicle for 3 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 20 publications
3
42
1
Order By: Relevance
“…28,29 In the current study, blood biochemistry showed no significant effect on hepatic function with LPS even though minor histological lesions were present in all LPS groups, suggesting that sufficient normal hepatic tissue is still present to preserve liver function. Even without lesions, hypoalbuminemia and hypoproteinemia are frequently observed with isoflurane or ketamine-xylazine anesthesia, 10,30 suggesting an effect on hepatic metabolism.…”
Section: Discussioncontrasting
confidence: 46%
“…28,29 In the current study, blood biochemistry showed no significant effect on hepatic function with LPS even though minor histological lesions were present in all LPS groups, suggesting that sufficient normal hepatic tissue is still present to preserve liver function. Even without lesions, hypoalbuminemia and hypoproteinemia are frequently observed with isoflurane or ketamine-xylazine anesthesia, 10,30 suggesting an effect on hepatic metabolism.…”
Section: Discussioncontrasting
confidence: 46%
“…The severity of an infection is negatively correlated to serum vitamin D concentrations. These findings proposed another important role for this vitamin in the progression of sepsis pathogenesis (11)(12)(13). The…”
Section: Introductionmentioning
confidence: 74%
“…Furthermore, vitamin D insufficiency may also be important in the pathogenesis of sepsis, the most fatal consequence of infection. In vitro and in vivo models of sepsis suggest that vitamin D treatment modulates proinflammatory cytokine production, deranged coagulation and activation of the vascular endothelium, as seen in sepsis syndromes [6,9,10].…”
Section: Introductionmentioning
confidence: 99%